KETERLIBATAN ORANG TUA PADA AKTIVITAS LITERASI DI RUMAH - Rachmawaty, Mia; Risina, Duana Fera (Jurnal Caksana : Pendidikan Anak Usia Dini, 2021)
Abstract Parental involvement is the key to children's success, including the success of children's literacy. The form of literacy involvement between parents and early childhood education units (PAUD) is shown by the activeness of parents in literacy programs that are aligned with activities at home. Childcare as a non-formal PAUD unit invites parents to optimize the intensity of involvement. During the pandemic, child care centers cannot operate normally so parents must be able to take care of children in conjunction with other jobs. This study is interested in how parents carry out literacy activities for children at home. The research subjects were 14 parents in child care centers who have children aged 4 to 6 years. Qualitative descriptive research method, data collection through interviews with results that explain that the involvement of parents in children's literacy activities at home still requires assistance from the teacher in developing types of literacy activities according to children's needs.